The Impact of Consumer Behaviour Megashift on Unilever's Product Strategy During COVID-19 Crisis - Annissa Nur Imani Fithry; Muhammad Irhas Zulfani Putra Hariyanto; Elok Sri Utami (UPT Penerbitan Universitas Jember, 2021)
The Covid-19 pandemic has made many changes. The changes that rapidly occur, resulting in the consumer's behaviour change in obtaining goods and services. Unilever is a global consumer goods corporation that manufactures everyday items such as soap and food. It is one of the oldest multinational corporations, with products sold in over 190 countries. During the Covid-19 outbreak, demand for products and services has plummeted, and Unilever has reacted strongly to the problem. This study aims to explore how Covid-19 affected Unilever and how Unilever improved the company's welfare. The research method used is descriptive. Data were collected from news articles, websites, and other reviews. To summarize the facts, Unilever is mostly unaffected by the Covid-19 epidemic because most of its products are considered needs and are widely recognized. Keywords: Consumer Behaviour, Unilever, Product Strategy, Covid-19, Impact